Антропологическое измерение социокультурной реальности общества знаний - Штанько, В. И. (НТУ "ХПИ", 2013)
Influence of modern information computer technologies and global information space on understanding of socio-culture reality and feature of human being in this reality is considered in this article. The special attention is paid on analysis of the problem of forming of"clip" consciousness, features of communication and construction of identity "I" in virtual reality.
Keywords: реальность виртуальная; сознание клиповое; идентичность; технологии информационные; технологии компьютерные